Edukasi Kesehatan Muskuloskeletal Berbasis Komunitas Untuk Meningkatkan Pengetahuan Lanjut Usia - Astri Anita (Pusmedia Group Indonesia, 2026)
Musculoskeletal health in older adults is an important aspect of maintaining quality of life; however, it often receives limited attention in promotive and preventive efforts. This community engagement activity aimed to improve the knowledge and skills of older adults in maintaining muscle and bone health through education and exercise demonstrations. The method used was an educative participatory approach conducted at the SALSA Gorontalo Community, involving 31 older adultsas participants. The activity included the delivery of educational materials on the aging process, fall risk, and the importance of physical activity, followed by discussion sessions and demonstrations of four muscle strengthening and balance exercises (sit-to-stand, heel raise, single leg stance, and marching in place) that can be performed independently at home. Evaluation was carried out descriptively through observation of participants’ engagement and their ability to understand and perform the exercises, along with verbal confirmation of participants’ subjective responses. The results showed that all 31 participants were enthusiastic, actively engaged in discussions, and able to understand and practice the exercises provided. In addition, 26 of the 31 participants (83.9%) reported increased understanding and a greater sense of comfort in their musculoskeletal condition, based on self-report. This activity demonstrates that the integration of education and exercise demonstrations is effective in improving knowledge and skills among older adults as part of promotive and preventive health efforts.